THE EFFECT OF DENSITY TO THE SURVIVAL RATE, GROWTH AND BIOCHEMICAL COMPOSITION OF FEMALE MANGROVE CRAB (SCYLLA OLIVACEA) CULTIVATED WITH SILVOFISHERY SYSTEM - Karim, Muhammad Yusri; Amri, Khairul; Azis, Hasni Yulianti; Nurfadilah; Alimuddin; Usman, Zainal (International Journal of Research -GRANTHAALAYAH, 2020)
Mangrove crab silvofishery system is one of the potential aquaculture activities to be developed because it is supported by the availability of extensive mangrove areas. This research was carried out in the Mangrove Area of Mandalle Village, Pangkep Regency, South Sulawesi. The study was aimed to determine the best density of survival, growth, and chemical composition of the body of female mangrove crabs (Scylla olivacea) maintained by the silvofishery system. The research container used a step cage made of bamboo measuring 2.25 m2 wide. Tested animals used were female mangrove crabs measuring 155 ± 1.0 g which were kept for 40 days. The study was designed using a randomized block design consisting of four density treatments with three replications each. The four densities were: 5,10, 15 and 20 crabs/cage. The results of the analysis of variance showed that the difference in density has a very significant effect (p <0.01) on the survival, growth and biochemical composition of the female body of mangrove crabs. The best survival, growth, and biochemical composition produced the best density of 5 and 10 individuals, while the lowest density was 20 individuals.